The Power to change : women in the Third World redefine their environment - Women's Feature Service (Project); Kali for Women (Organization) (New Delhi : Kali for Women, 1992)
On the social and economic condition of women in Latin America, Africa, and Asia; contributed articles.
Keywords: Women in development -- Developing countries -- Case studies; Women -- Developing countries -- Social conditions